Public attitudes to, and perceived impacts of 20mph (32 km/h) speed limits in Edinburgh: An exploratory study using the Speed Limits Perceptions Survey (SLiPS). (January 2022) - Williams, Andrew James; Manner, Jillian; Nightingale, Glenna; Turner, Kieran; Kelly, Paul; Baker, Graham; Cleland, Claire; Hunter, Ruth; Jepson, Ruth
Highlights: The Speed Limits Perception Survey (SLiPS) measures perceptions of 20mph limits. Support for 20mph limits in Edinburgh rose after an increase in 20mph streets. Perceived walking or child safety did not change after 20mph limit implementation. Further research will examine whether these changes in perception affect behaviour. Studies of changes in perceptions will support transport policy implementation. Abstract: Between 2016 and 2018 a policy was implemented to increase the proportion of 20mph (32km/h) streets in Edinburgh, UK from approximately 50% to 80%, providing the opportunity to evaluate how behaviour and public perceptions change over time. This is important as negative public responses have been reported to limit the implementation of transport policies and may reduce the effectiveness of the policy. The Speed Limits Perception Survey (SLiPS) was developed to assess changes in public perceptions from baseline to 6 and 12 months post-implementation. We collected 3, 485 individual responses to the survey, 64.6% (n = 2, 253) of which included complete perceptions data. Using exploratory factor analysis, the following perception factors were identified: i) Detraction and resistance, ii) Support, iii) Rule following, iv) Child safety, and v) Walking safety . Following the 20mph implementation at 6–12 months: Support (ii) and Rule following (iii) had increased; Detraction and resistance (i) had decreased; and Child safety (iv) and Walking safety (v) had not changed significantly. These findings indicate that the public in Edinburgh became more positive towards the policy once it was implemented. However, more extensive policy or ongoing communication of the safety benefits of 20mph limits are needed to increase perceptions of safety that might lead to increased walking and cycling. Future research should aim to understand how those implementing speed limit interventions can positively influence public perceptions and how public perceptions about speed limits influence behaviour.